Biometric based signature authentication scheme for cloud healthcare data security - Thangarasu, G. (Springer Verlag, 2019)
Cloud Computing is a recent and fastest growing area of development in healthcare. Cloud-based healthcare management services are considered as an effective way to manage the data related to healthcare. However, the major problem associated with the healthcare management service is data security. It leads to tax, bank, insurance and medical fraudulence. Hence, retrieval of data onto more secured access is required to improve the security of medical records of healthcare services. In this research, proposed a biometric based signature authentication scheme with neural network for cloud healthcare data security. The neural network is used in this scheme for the accuracy of retrieving the clinical data onto the cloud. The neural network acquires biometric signature through biometric sensor processed with quality checker for effective authentication. This network also has support in terms of statistical learning of the clinical datasets. After various experiments, it is concluded that the proposed method provides faster results with higher sensitivity, specificity with accuracy. Â© Springer Nature Switzerland AG 2019.